PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF STUDENTS' LEARNING OF DRAWING (Multidisciplinary Journal of Science and Technology, 2024)
The article deals with the problems of formation of spatial thinking and spatial imagination in pupils of VIII-X classes. Psychological and pedagogical aspects of studying drawing by pupils are substantiated. Types and classifications of thinking are given.